A Survey of Nitrate and Nitrite Concentrations in Conventional and Organic‐Labeled Raw Vegetables at Retail. Issue 5 (7th April 2015) - Nuñez de González, Maryuri T.; Osburn, Wesley N.; Hardin, Margaret D.; Longnecker, Michael; Garg, Harsha K.; Bryan, Nathan S.; Keeton, Jimmy T.
Abstract A national survey of the nitrate (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz4wpqx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NO 3−</alternatives>) and nitrite ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz4wprf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NO 2−</alternatives>) concentrations in raw and highly consumed vegetables available at retail in the United States was conducted. A total of 194 samples of fresh broccoli, cabbage, celery, lettuce, and spinach categorized as conventional or organic by label were collected from 5 major cities in different geographic regions of the United States and analyzed to determine <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz4wptg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NO 3−</alternatives> and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz4wgq1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NO 2−</alternatives> concentrations. There were no differences in the mean <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz4wgtk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NO 2−</alternatives> values of conventional compared with organic vegetables taken from the 5 metropolitan areas. However, significant differences in mean pairwise comparisons between some conventional and organic vegetables for <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz4wgv3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NO 3−</alternatives> content were observed. The mean <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz4wgwm" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NO 2−</alternatives> concentration of both conventional and organic vegetables ranged between 0.1 and 1.2 mg/kg of fresh weight (FW) with the exception of conventional spinach that contained 8.0 mg/kg FW. Mean <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz4wgzn" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NO 3−</alternatives> contents of conventional broccoli, cabbage, celery, lettuce, and spinach were 394, 418, 1496, 851, and 2797 mg/kg FW, respectively, while their organic‐labeled counterparts averaged 204, 552, 912, 844, and 1318 mg/kg FW. In most cases, organic vegetables were numerically lower in <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz4wh15" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NO 3−</alternatives> content than their conventional counterparts. Based on survey results, the finding that low <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz4wgbb" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NO 3−</alternatives> levels were observed in some organic vegetables in different cities may warrant further study to determine if true differences exist, due to production practices, seasonal differences, and the magnitudes of those differences. Furthermore, the geographic differences in <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz4wgkz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NO 3−</alternatives> content of vegetables may flaw estimates of daily <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz4wgjf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NO 2−</alternatives> and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgjkz4wgph" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> NO 3−</alternatives> exposure.